The return : fathers, sons, and the land in between - Matar,Hisham (Random House, 2016)
In 2012, after the overthrow of Qaddafi, the novelist Hisham Matar journeys to his native Libya after an absence of thirty years. When he was twelve, Matar and his family went into political exile. Eight years later Matar's father, a former diplomat and military man turned brave political dissident, was kidnapped from the streets of Cairo by the Libyan government and is believed to have been held in the regime's most notorious prison. Now, the prisons are empty and little hope remains that Jaballah Matar will be found alive. Yet, as the author writes, hope is "persistent and cunning."